Primary Aorto-Enteric Fistula With a Subsequent Secondary Aorto-Enteric Fistula - Kärjä, Iris (Elsevier, 2025)
Objective Primary aortoenteral fistula (PAEF) is a connection between the gastrointestinal tract and the aorta that occurs without previous aortic surgery. The aetiological factors include, but are not limited to, aneurysm, infection, and tumours. It is a life threatening condition if untreated and requires emergency vascular surgical repair. A secondary aortoenteric fistula (AEF) can occur to a previously reconstructed aorta. This case report presents a unique case of a male patient who developed a primary AEF and subsequent secondary AEF with successful surgical outcomes, suggested to be due to tuberculous aortitis.
Report The patient was diagnosed and treated for tuberculosis and developed a saccular aneurysm within 6 months. The PAEF was surgically corrected with a tubular graft using a bovine pericardial patch, the defect in duodenum was sutured, and a retrocolic omental flap was created between the duodenum and aorta. He developed a small stable pseudoaneurysm during follow up, and then a secondary AEF two and a half years later, where a connection between the pseudoaneurysm and duodenum was corrected using a new bovine aorto–aortic interposition graft using a bovine pericardium patch. The defect in the duodenum was also sutured in two layers and a new omental flap was created.
Discussion The mortality rate of AEF is high and it is very unlikely that a patient will survive two AEFs without major complications. It is believed that there are extremely few double AEF cases described in the literature. The aetiological factor in the development of PAEF in this case was most likely the patient’s aortic aneurysm, which was most likely of mycotic origin due to tuberculosis. The patient developed a pseudoaneurysm during follow up and it is uncertain whether the pulsatile pressure of the pseudoaneurysm led to the recurrence of the AEF.